Se Nanowire Crystal Formation via Oxidation of 2D HfSe2: A Solid-State, In Situ Reaction Coupling for Heterogeneous Integration Technologies - Sahota, S.; Chircă, I.; Burton, OJ; Yu, H.; Rimmer, M.; Yang, J.; Park, K.; Summers, A.; Mertdinc-Ulkuseven, S.; Lindley, M.; Haigh, SJ; Hofmann, S. (American Chemical Society (ACS), 2025)
Effective heterogeneous integration of low-dimensional nanomaterials in applications ranging from quantum electronics to biomedical devices requires a detailed understanding of different formation and interfacing reactions and ability to synergize these processes. We report the formation of 1D Se nanowires via low temperature (30-150◦C) atmospheric oxidation of 2D HfSe2 crystals. The localised, surface-bound process starting from exfoliated HfSe2 flakes on SiO2/Si wafer support does not involvewet chemistry and allows us to implement optical operando reaction screening and explore the relevant parameter space and underpinning mechanisms. Hf oxidation frees Se at the buried hafnia/HfSe2 interface, which segregates as amorphous Se forming aggregates, blisters and interfacial films. We show that upon diffusion to the stack surface this Se can crystallise into trigonal Se nanowires with diameters ranging from ≈ 45 nm to 1.9 μm and lengths up to 43 μm depending on temperature and process time. We discuss the coupled reaction kinetics, pathways for application-relevant integrated process design and connect diverse literature on oxidation of transition metal dichalcogenides, Se polymerisation and crystallisation studies, and prior synthetic strategies for producing Se nanowires.
Keywords: Chemical Sciences; Physical Chemistry; Nanotechnology; Engineering